Assessment of Healthcare Utilization among Women Experiencing Childbirth in Suburban Nepal - Xu, Shelly; D.O., Cyril Blavo; Marahatta, Sujan Babu; Banjara, Mayur; Amatya, Rakchya; Hardigan, Patrick; Anderson, Nadia (Journal of Health Promotion, 2019)
The postnatal period (birth to 6 weeks of age) is a high-risk period for mothers and their newborns. Despite significant improvements in the Nepalese healthcare system over the last decade, there is still a high incidence of maternal and neonatal deaths during the postnatal period. These factors, in addition to existing socioeconomic barriers, discourage many women from returning to these facilities for postnatal care. This study therefore, aims to determine the extent of healthcare utilization among women with recent childbirth experience in the Mahalaxmi municipality in the Lalitpur district of Nepal. This study is descriptive cross-sectional needs assessment utilizing a pre-tested survey instrument administered to ninety-eight women who were randomly selected from the semi-urban Mahalaxmi municipality. All the respondents reported that they received ante-natal care during their pregnancy. A majority of the women reported that they received perinatal care from physicians. The results of the study showed that although there was a significantly high utilization of ante-natal and perinatal care among women with recent childbirth experience, most of the women were unaware of the availability or necessity of postnatal care, despite the accessibility of physicians and healthcare facilities.